Injury prevalence among cricket athletes in East Java: A cross-sectional study - Ali Ridho Fadlurrahman Najib (CV Rezki Media, 2025)
Background: Cricket has a risk of injury that needs to be considered, especially for athletes in East Java. This study aims to understand the prevalence of injuries in East Java cricket athletes, including the type, location, cause, time of occurrence, and treatment, as an effort to prevent and improve athlete performance. Objectives: This study aims to determine the prevalence, types, causes, timing, and management of injuries among cricket athletes in East Java. Methods: This study uses non-experimental descriptive quantitative methods, with a cross-sectional study and total sampling technique. 25 Indonesian East Java Province Cricket athletes with an age of 22.68+2.32, height of 163.2+6.78, and weight of 60.32+10.06, consisting of 13 male athletes and 12 female athletes, were involved in this study. This research instrument used a questionnaire to collect data. Data were analyzed using percentage analysis. Results: The results showed that abrasions (36%) and muscle cramps (20%) were the most frequent injuries, especially affecting the lower extremities (56%). Overtraining (52%) was the leading cause, and injuries mainly occurred during training (52%). The RICE method was the most frequently applied treatment (60%). Conclusions: This study highlights the need for structured training programs and preventive strategies to reduce the incidence of injuries.